Multigestação em usuárias de unidades básicas de saúde no município de Barbalha: opção ou planejamento familiar ineficaz - Oliveira, Maria das Dores Rolim de (2007)
The study objective was to evaluate which variables may influence high fertility rates in the Barbalha city and to identify the existent lack in family planning assistance which may lead to ineffective approach in the Health Family Program. A 100% of pregnant women with 2 live children at least have been followed on the pre-natal care Services of Basic Health Units of Barbalha city and were included in the study. The women answered a 21 objective question questionnaire. A total of 81 multiparous women were enrolled in the study, aging 18 to 49 years old. A 96.3% declared have had sometime used a contraceptive method, from which 80.4% mentioned had received it in the same Basic Health Unity, even though just 42.3% have mentioned been assisted by the Family Planning assistance program. Around 32.1% of women have said were not taking a contraceptive method of their preference and 73.9% of the subjects have not plarmed to get pregnant currently. Discussion: In spite of the satisfactory Health Family Program structure (97.1%), fertility rate is still high and the grate majority of women have undesired pregnancy. This can be due to low efficacy of Family Planning assistance offered, with lack of orientation and little variety of contraceptive methods available.